Green Purchase Behavior and Social Practices Approach - Ghouri, Arsalan; A. Haq, Mirza (Management Research Journal, 2018)
Green purchase behavior (GPB) is not constant and vary in different contexts. This study aims to analyze the mediation impact of green advertisement (GA) on the relationship between the environmental concern (EC), social influence (SIN), self image (SIM), and GPB. 458 responses considered to apply structural equation model test and mediation analysis to evaluate the framework model of the study. The study employed the social practices approach to integrate GPB. The study concludes that the government, marketers and educators can increase the awareness of environmental deterioration and enhance the green purchase behavior by EC, SIN, and SIM with the presence of GA. Government can also further initiates the green policies and strategies. The findings further posit that EC, SIN, and SIM, with the presence of GA, can increase the GPB, and people become greener and environment conscious in their routine life. In the end, future directions and limitations discussed.